(untitled) (Research, Society and Development, 2022)
This research aims to introduce concepts, analyze and identify how the research fields of public security and traditional communities are currently interrelated with Human Ecology in what concerns scientific productivity. The methodological approach used is the systematic literary research, the content analysis by Bardin, the bibliometric analysis of articles published in scientific journals between January 1, 2011 and December 31, 2021 whose keywords include public security; Human Ecology and traditional and rural people and communities. Thus, this paper establishes the main authors, journals, countries that stand out in what regards the publication of researches, the methodologies used in these works and the existence or not of bibliometric concepts such as Lotka’s law and Bradford’s law.